2004
DOI: 10.1063/1.1739296
|View full text |Cite
|
Sign up to set email alerts
|

Position and momentum observables on R and on R3

Abstract: Abstract. We characterize all position and momentum observables on R and on R 3 . We study some of their operational properties and discuss their covariant joint observables.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 14 publications
0
39
0
1
Order By: Relevance
“…In our previous article [11] we have shown that these conditions are satisfied exactly when there is a probability measure ρ :…”
Section: Position and Momentum Observablesmentioning
confidence: 89%
“…In our previous article [11] we have shown that these conditions are satisfied exactly when there is a probability measure ρ :…”
Section: Position and Momentum Observablesmentioning
confidence: 89%
“…The sole requirement of boost covariance without further assumptions is not enough to lead to the form (7). It is interesting that there are even commutative boost covariant observables which are not smearings of P. This is illustrated in the following example.…”
Section: Smearingsmentioning
confidence: 94%
“…Compared to (4), here we have the additional requirement of boost invariance. It is proved in [7] that E is a position observable exactly when E = Q ρ for some probability measure ρ.…”
Section: Relativistic Approachmentioning
confidence: 99%
“…Here by an approximate position measurement we mean an observable F , which is covariant for position shifts, and commutes with momentum, so that F (X − q) = W (q, p)F (X)W * (q, p). These are necessarily of the form F ρ = µ * E Q ρ for some measure µ (see, e.g., 21 ). Suppose that we have such an approximate position measurement and, similarly, an approximate momentum measurement given by a noise measure ν.…”
Section: A Covariant Phase Space Observablesmentioning
confidence: 99%